Leprosy and gender in Brazil: trends in an endemic area of the Northeast region, 2001-2014 - Eliana Amorim de Souza; Anderson Fuentes Ferreira; Reagan Nzundu Boigny; Carlos Henrique Alencar; Jorg Heukelbach; Francisco Rogerlândio Martins-Melo; Jaqueline Caracas Barbosa; Alberto Novaes Ramos Jr (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To analyze, stratifield by gender, trends of the new case leprosy detection rates in the general population and in children; of grade 2 disability, and of proportion of multibacillary cases, in the state of Bahia, Brazil from 2001 to 2014. METHODS A time series study based on leprosy data from the National Information System for Notifiable Diseases. The time trend analysis included Poisson regression models by infection points (Joinpoint) stratified by gender. RESULTS There was a total of 40,054 new leprosy cases with a downward trend of the overall detection rate (Average Annual Percent Change [AAPC = -0.4, 95%CI -2.8-1.9] and a non-significant increase in children under 15 years (AAPC = 0.2, 95%CI -3.9-4.5). The proportion of grade 2 disability among new cases increased significantly (AAPC = 4.0, 95%CI 1.3-6.8), as well as the proportion of multibacillary cases (AAPC = 2.2, 95%CI 0.1-4.3). Stratification by gender showed a downward trend of detection rates in females and no significant change in males; in females, there was a more pronounced upward trend of the proportion of multibacillary and grade 2 disability cases. CONCLUSIONS Leprosy is still highly endemic in the state of Bahia, with active transmission, late diagnosis, and a probable hidden endemic. There are different gender patterns, indicating the importance of early diagnosis and prompt treatment, specifically in males without neglecting the situation among females.